Thermal regulation of algae cultures in raceway ponds utilizing ground heat: Improving techno-economic feasibility and process sustainability of large-scale algae production in Qatar - Rihab, Rasheed (2023)
There is an increasing drive for developing sustainable alternatives for fuels, foods, feeds, and chemicals. Algae can play a significant role in this, however the commercialization of microalgal biomass is still limited for techno-economic reasons. Open raceway ponds are some of the most competitive systems to produce algae on a large scale, however productivities and techno-economics can be unfavorable when temperature fluctuations cause sub-optimal conditions. Maintaining temperatures nearer to strain-optima through thermal regulation has been shown to increase productivities, however the techno-economic impact of implementation has yet to be addressed. In this study the effect of ground-heat exchanger implementation for thermal regulation of open raceway ponds was evaluated in terms of productivity, production costs and process sustainability. Multiple thermal regulation scenarios were evaluated for two microalgae strains from Qatar, Pichochlorum maculatumandNannochloris atomus, and it was projected that thermal regulation could increase annual biomass yields up to 10.0 and 69.6 %, respectively. Biomass production costs were found to be reduced as much as 29.5 %, depending on strain and regulation scenario. Furthermore, a sensitivity analysis identified further means by which energy requirements and production costs could be reduced by 18.9 and 67.2 %, respectively, reaching a biomass production cost of 6.21 €·kg−1.